VDDDAs-based Voltage-mode Multiphase Sinusoidal Oscillator - Sunti Tuntrakool; Montree Kumngern; Winai Jaikla (My University, 2016)
The design of voltage-mode multiphase sinusoidaloscillator (MSO) is presented. The odd phase system can be realizedusing voltage differencing differential difference amplifier (VDDDA)-basedlossy integrators. The condition of oscillation and frequency of oscillationcan be controlled independently through adjusting the bias current of theVDDDA. The low output impedances facilitate easy driving an external loadwithout additional voltage buffers. The proposed MSO provides odd phase signalsthat are equally spaced in phase and equal amplitude. The circuit requires oneVDDDA, two resistors and one grounded capacitor per phase without externalresistor and additional current amplifier. The results of PSPICE simulationsusing 0.18ms TSMC CMOS technologyare included to verify theory.
Keywords: Mode (computer interface); Analog and Mixed-Signal Circuit Design